Fish wariness is a more sensitive indicator to changes in fishing pressure than abundance, length or biomass. Issue 4 (16th March 2017) - Goetze, Jordan S.; Januchowski‐Hartley, Fraser A.; Claudet, Joachim; Langlois, Tim J.; Wilson, Shaun K.; Jupiter, Stacy D.
Abstract: Identifying the most sensitive indicators to changes in fishing pressure is important for accurately detecting impacts. Biomass is thought to be more sensitive than abundance and length, while the wariness of fishes is emerging as a new metric. Periodically harvested closures (PHCs) that involve the opening and closing of an area to fishing are the most common form of fisheries management in the western Pacific. The opening of PHCs to fishing provides a unique opportunity to compare the sensitivity of metrics, such as abundance, length, biomass and wariness, to changes in fishing pressure. Diver‐operated stereo video (stereo‐DOV) provides data on fish behavior (using a proxy for wariness, minimum approach distance) simultaneous to abundance and length estimates. We assessed the impact of PHC protection and harvesting on the abundance, length, biomass, and wariness of target species using stereo‐DOVs. This allowed a comparison of the sensitivity of these metrics to changes in fishing pressure across four PHCs in Fiji, where spearfishing and fish drives are common. Before PHCs were opened to fishing they consistently decreased the wariness of targeted species but were less likely to increase abundance, length, or biomass. Pulse harvesting of PHCs resulted in a rapid increase in the wariness of fishes but inconsistent impacts across the other metrics. Our results suggest that fish wariness is the most sensitive indicator of fishing pressure, followed by biomass, length, and abundance. The collection of behavioral data simultaneously with abundance, length, and biomass estimates using stereo‐DOVs offers a cost‐effective indicator of protection or rapid increases in fishing pressure. Stereo‐DOVs can rapidly provide large amounts of behavioral data from monitoring programs historically focused on estimating abundance and length of fishes, which is not feasible with visual methods.